Of Feral Faculty and Magisterial Mowglis: The Domestication of Junior Faculty. Issue 171 (3rd September 2015) - Reddick, Richard J.
Abstract : This chapter presents an assistant professor's scholarly personal narrative at the precipice of promotion, and reveals how the feral child metaphor might aptly describe many junior professors' experiences as they navigate a path toward tenure. This chronicling of mentorship in sometimes unexpected venues may aid new faculty and those invested in their success in both earning tenure and retaining them in the field.